Household size and Socio-Economic Development in Kibuku District, Uganda: A Cross-sectional study. - Herbert Tom Kinobere; Edmand Bakashaba (Student's Journal of Health Research, 2022)
Background of the study  The purpose of the study was to establish the effect of household size on socio-economic development in the Kibuku district by establishing the average size of households, determining the level of socio-economic development among households, and establishing the relationship between household size and socio-economic development in the Kibuku district.  Methodology: A descriptive comparative, correlational, and cross-sectional survey design was employed for this study. A sample size of 308 households was selected using the Slovene formula.  Results: Of the 300 respondents to the study, 180 were females and 120 were males. Also, 86 of the 300 selected households have 1-5 members. The findings also revealed that a big number of households in the Kibuku district depend on their parents, there were no improved medical care services, and limited to clean water in the district as surgeries and complicated health issues are carried out from the neighboring districts. Conclusion: The level of social economic development in the Kibuku district was still wanting and below the national average. There was also a significant relationship between household size and social economic status.  Recommendations Based on the findings, there is a need to sensitize the population in the Kibuku district about the use of family planning to reduce the dependence burden on household heads. Also, there is a need to awaken the government to provide social infrastructures such as electricity and tarmacked roads to increase the level of employment opportunities and household incomes of the locals.